Statistical analysis of PV penetration impact on residential distribution grids. (December 2022) - Palahalli, Harshavardhan; Maffezzoni, Paolo; Daniel, Luca; Gruosso, Giambattista
Abstract: This paper presents a comprehensive approach to the probabilistic analysis of residential distribution grid injected by distributed PV sources. The approach is data-driven and is able to deal with the general scenario that includes the uncertainty of correlated PV sources and of statistically independent consumer loads. The novel method adopts a Gaussian-Mixture-Model for correctly representing PV sources correlation and a fresh probabilistic analysis technique employing Multi-Expansion polynomial chaos. Numerical experiments carried out on the Non-Synthetic European low voltage test system, highlight the importance of the comprehensive modeling strategy in order to realistically quantify uncertainty impact on the grid.